Role of morphology in electrochemical hydrogen storage using binary DyFeO3-ZnO nanocomposites as electrode materials. (11th June 2021) - Baladi, Mahin; Valian, Movlud; Ghiyasiyan-Arani, Maryam; Salavati-Niasari, Masoud
Abstract: Hydrogen storage technology is one of the most challenging issues due to the increasing demand for fossil fuel replacement and the reduction of greenhouse gas emissions. In the current paper, the main aim is one-step and eco-friendly preparation of DyFeO3 -ZnO nanocomposites using Barberry fruit extract as natural precursor (with the role of both fuel and capping agent) to compare with various conventional carboxylic acids. To further examine, the effect of different parameters like calcination temperature and the type of the chelating agent was scrutinized to acquire optimum shape, structure, morphology and size of the obtained products. This is the first effort on the investigation of the hydrogen storage capacity of DyFeO3 -ZnO nanocomposites in terms of role of morphology. The electrochemical hydrogen storage capacity of obtained DyFeO3 -ZnO nanocomposites was studied mediated by chronopotentiometry charge-discharge methods in KOH medium. The synthesis of nanocomposites in the presence of chemical or natural capping agent (carboxylic acids or Barberry fruit extract) led to different morphologies which affects to the electrochemical performance. As a result, the electrode which is provided by plate-like DyFeO3 -ZnO nanocomposites performed 600.11 mAh/g discharge capacity compared with other samples. Based on the obtained results, DyFeO3 -ZnO nanocomposites can be promising compounds to improve the electrochemical performance of hydrogen storage. Highlights: Hydrogen storage ability investigated for DyFeO3 -ZnO nanocomposites. Green and facile pechini method for synthesis of DyFeO3 -ZnO nanocomposites was designed. A series of carboxylic acid against barberry extract fruit have been compared to a study of morphology.